Systemic inflammation is an important risk factor and predictor of graft loss and mortality one year after kidney transplantation - Heldal, Torbjørn F.; Åsberg, Anders; Ueland, Thor; Reisæter, Anna V.; Pischke, Søren E.; Mollnes, Tom E.; Aukrust, Pål; Reinholt, Finn P.; Hartmann, Anders; Heldal, Kristian; Jenssen, Trond G. (Frontiers in Immunology, 2025)
BackgroundAn inflammatory environment following kidney transplantation is associated with increased risk of graft loss and mortality, however, evaluation of systemic inflammation is not implemented in structured risk assessment in kidney transplant recipients. Long-term results after transplantation are not satisfactory, and thus tools addressing these issues are needed. In this study, we tested the associations and predictive abilities of a predefined systemic inflammation score one year after transplantation on death-censored graft loss and mortality.MethodsWe included 805 patients who underwent kidney transplantation between 2013 and 2017 at the Oslo University Hospital, Rikshospitalet. The inflammation score included five specifically selected biomarkers known to reflect various inflammatory pathways and to be associated with adverse outcomes following transplantation. The score was assessed in relation to outcomes in models with established risk factors. Discriminatory analyses were performed using Harrell´s C-statistic, and model assessment were evaluated using internal validation, calibration, and likelihood ratio tests.ResultsThe median follow-up time was 6.4 years. There were 168 deaths (20.9%) and 42 graft losses (5.2%). The inflammation score one year after transplantation was significantly associated with graft loss (P<0.001) and mortality (P<0.001). The diagnostic performance of the model for graft loss revealed a c-statistic of 0.77 both with and without histological data. The diagnostic performance for mortality displayed a c-statistic of 0.79. In all tested scenarios, the model fit significantly improved after including the inflammation score.ConclusionsThese results suggest a strong association between systemic inflammation one year after transplantation and both graft loss and mortality. Predictive models including the inflammation score and established risk factors were particularly informative when considering mortality. Evaluation of systemic inflammation using this score could be an important tool for risk-assessment after transplantation.